Condura Croatica – a revision of the structural drawings - Jelić, Anita; Pešić, Mladen (Sailing through History. Reading the Past – Imagining the Future: Proceedings of the 16th International Symposium on Boat & Ship Archaeology ISBSA 16, 2024)
Since 1994, two wooden boats known as Condurae Croaticae have been exhibited in the small Museum of Nin Antiquities. Over time, significant degradation has been observed on the wooden elements. This led to a comprehensive conservation-restoration procedure launched in 2017. During these works, a gap was noticed between the frames and planking measuring up to 5 cm, which led to a revision of the structural drawings of these vessels. With the help of new digital technologies and the creation of ship lines based on images, efforts were made to determine whether their current condition aligns with its first interpretation presented in the Museum.